Analysis of C-Reactive Protein (CRP) Levels in Venous and Capillary Blood Samples with Immunoturbidimetric Methods: Analisa Kadar C-Reactive Protein (CRP) Pada Sampel Darah Vena Dan Darah Kapiler Dengan Metode Imunoturbidimetri - Bastian, Bastian; Sari, Indah; Pratama, Feronica Putri (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Inflammation or inflammation occurs due to bacterial infection, detection of inflammatory infection can be done by laboratory tests. An examination that can help diagnose and detect abnormalities in the body. One of the parameters for examining inflammation markers is C-Reactive Protein (CRP). CRP examination usually uses venous blood because venous blood is more often used in laboratory examinations. The purpose of this study was to determine differences in CRP levels in venous and capillary blood. This study uses a posttest only design research. Samples were taken from DIV Technology Medical Laboratory IkesT Muhammadiyah Palembang students with total sampling technique. The research was carried out at the Hematology Laboratory of IKesT Muhammadiyah Palembang on December 21, 2021. Based on the results of research that has been carried out on the analysis of C_Reactive Protein levels in venous blood and capillary blood samples using the immunoturbidemteri method, the results showed that the average CRP level of venous blood was 9.6 and average the average capillary blood CRP level was 8.33. Thus it can be concluded that there is no significant difference in the examination of CRP levels in venous and capillary blood.